Strawberries and Cream: The Relationship Between Food Rejection and Thematic Knowledge of Food in Young Children - Pickard, Abigail; Thibaut, Jean-Pierre; Lafraire, Jérémie (Frontiers in Psychology, 2021)
Establishing healthy dietary habits in childhood is crucial in preventing long-term repercussions, as a lack of dietary variety in childhood leads to enduring impacts on both physical and cognitive health. Poor conceptual knowledge about food has recently been shown to be a driving factor of food rejection. The majority of studies that have investigated the development of food knowledge along with food rejection have mainly focused on one subtype of conceptual knowledge about food, namely taxonomic categories (e.g. vegetables or meat). However, taxonomic categorization is not the only way to understand the food domain. We also heavily rely on other conceptual structures, namely thematic associations, in which objects are grouped because they share spatial-temporal properties or exhibit a complementary relationship (e.g. soft-boiled egg and soldiers). We rely on such thematic associations between food items, which may not fall into the same taxon, to determine the acceptability of food combinations. However, the development of children’s ability to master these relations has not been systematically investigated, nor alongside the phenomenon of food rejection. The present research aims to fill this gap by investigating i) the development of conceptual food knowledge (both taxonomic and thematic) and ii) the putative relationship between children’s food rejection (as measured by the Child Food Rejection Scale) and both thematic and taxonomic food knowledge. A proportional (A:B::C:?) analogy task, with a choice between taxonomic (i.e. bread and pasta) and thematic (i.e. bread and butter) food associates, was conducted on children between three and seven-years-old (n = 85). The children were systematically presented with either a thematic or taxonomic food base pair (A:B) and then asked to extend the example type of relation to select the respective thematic or taxonomic match to the target (C:?). Our results revealed, for the first time, that increased levels of food pickiness were significantly predictive of poorer food identification and decreased thematic understanding. These findings entitle us to hypothesize that knowledge-based food education programs to foster dietary variety in young children, should not only aim to improve taxonomic understanding of food, but also thematic relations.